ANALISIS PENGGUNAAN REKAM MEDIS ELEKTRONIK DENGAN KEPUASAAN TENAGA KESEHATAN DI PUSKEMAS KARANG JOANG KOTA BALIKPAPAN - Andry Rachmadani; Nila Trisna Yulianti; Dewi Ari Sasanti; Heni Elmiani Sari; Pradea Wulandari (Politeknik Unggulan Kalimantan, 2025)
The use of electronic medical records (EMR) is one of the efforts to digitize health services that aims to improve the efficiency and quality of services. This study aims to analyze the relationship between the use of EMR and the level of satisfaction of health workers at the Karang Joang Health Center, Balikpapan City. This study uses a quantitative approach with a cross-sectional design. Data were collected through questionnaires distributed to health workers who use the EMR system in carrying out their daily tasks. The aspects analyzed include ease of use, system reliability, speed of data access, and technical support. The results showed that the majority of respondents felt that the use of EMR was quite helpful in work efficiency. Statistical analysis showed (p <0.05) which means there is a relationship. Based on these findings, it can be concluded that although EMR provides benefits in managing patient data, improving system quality and user training are still needed to optimize user satisfaction. The recommendation of this study is to strengthen digital infrastructure and continuous training for health workers to maximize the use of EMR.